The The Effect of Green Accounting and Carbon Accounting on Production Sustainability in Financial Performance in Agribusiness Companies - Ramadhan, Charisma Bayu; Pandin, Maria Yovita R. (Manunggal Halim Jaya, 2025)
This research aims to describe the evolution of internal audit, focusing on identifying the most productive and cited articles, authors, countries, and institutions. The study used bibliometric analysis with VOSviewer software based on Scopus data, covering 490 articles published from 2017–2023. Data was collected using the